2020
DOI: 10.1111/ejh.13518
|View full text |Cite
|
Sign up to set email alerts
|

Midostaurin in combination with chemotherapy is most effective in patients with acute myeloid leukemia presenting with high FLT3‐ITD allelic ratio who proceed to allogeneic stem cell transplantation while in first complete remission

Abstract: Objectives Midostaurin, a multikinase and FLT3 inhibitor, is the first non‐chemotherapy agent approved and widely adopted for the treatment of FLT3‐ITD acute myeloid leukemia (AML). Yet, its role in improving survival of patients referred to allogeneic stem cell transplantation (allo‐SCT) in first complete remission (CR1) needs to be defined. Methods This multicenter study retrospectively evaluated the outcome of 119 FLT3‐ITD AML patients [59 (49.6%) males and 60 females] intensively treated between 2015 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Midostaurin therapy improved OS specifically in patients with high AR and only midostaurin therapy and allo-SCT in first CR were found as positive predictors for OS. 92 The effect of midostaurin to prevent relapse in FLT3-ITD carrying patients (18–70 years old) subjected to allo-SCT showed that midostaurin plus standard chemotherapy could not improve relapse-free survival (RFS) (89%) significantly as compared to only chemotherapy arm (76%), concluding the addition of midostaurin as maintenance therapy following allo-SCT could be only beneficial for some patients with FLT3-ITD AML. 93 Midostaurin with standard chemotherapy for older FLT3-ITD AML patients (18–70 years) was shown to be safely effective as induction therapy.…”
Section: Clinically Approved Flt3 Inhibitors In Therapymentioning
confidence: 99%
“…Midostaurin therapy improved OS specifically in patients with high AR and only midostaurin therapy and allo-SCT in first CR were found as positive predictors for OS. 92 The effect of midostaurin to prevent relapse in FLT3-ITD carrying patients (18–70 years old) subjected to allo-SCT showed that midostaurin plus standard chemotherapy could not improve relapse-free survival (RFS) (89%) significantly as compared to only chemotherapy arm (76%), concluding the addition of midostaurin as maintenance therapy following allo-SCT could be only beneficial for some patients with FLT3-ITD AML. 93 Midostaurin with standard chemotherapy for older FLT3-ITD AML patients (18–70 years) was shown to be safely effective as induction therapy.…”
Section: Clinically Approved Flt3 Inhibitors In Therapymentioning
confidence: 99%
“…The FDA approved midostaurin to be used in combination with standard induction therapy with cytarabine and daunorubicin and consolidation therapy with cytarabine in FLT3-mutated newly diagnosed young (18–59 years) patients with AML [ 22 ]. Ofran et al [ 23 ] investigated the roles of midostaurin in patients’ survival who were initially treated with intensive chemotherapy plus midostaurin and then proceed to allo-stem-cell transplantation (SCT) in the first complete remission (CR) [ 23 ]. In a multivariate analysis, midostaurin use and allo-SCT in CR1 were the most significant factors affecting overall survival (OS).…”
Section: Combination Therapy Targeting the Flt3 Signaling Pathwaymentioning
confidence: 99%
“…In a multivariate analysis, midostaurin use and allo-SCT in CR1 were the most significant factors affecting overall survival (OS). Midostaurin incorporation into chemotherapy regimens significantly improved CR + CR, with incomplete hematologic recovery rates ( p = 0.002) and reduced relapse rates ( p = 0.02); it was also remarkably advantageous for FLT3-ITD high-allelic ratio patients (2-year OS of 82%) [ 23 ].…”
Section: Combination Therapy Targeting the Flt3 Signaling Pathwaymentioning
confidence: 99%